Oregano Essential Oils Promote Rumen Digestive Ability by Modulating Epithelial Development and Microbiota Composition in Beef Cattle - Zhang, Rui; Wu, Jianping; Lei, Yu; Bai, Yunpeng; Jia, Li; Li, Zemin; Liu, Ting; Xu, Yangbin; Sun, Jianxiang; Wang, Ying; Zhang, Ke; Lei, Zhaomin (Frontiers in Nutrition, 2021)
This study aimed to explore the effects of oregano essential oils (OEO) on the rumen digestive ability using multi-omics sequencing techniques. Twenty-seven castrated Pingliang red cattle were randomly separated into three groups (3 cattle/pen; n = 9) and fed on a daily basal diet supplemented with 0 (Con group), 130 mg (L group), and 260 mg (H group) OEO. The finishing trial lasted for 390 days, and all cattle were slaughtered to collect rumen tissue and content samples. We found that the rumen papillae length in the H group was higher than in the Con group. Amylase concentrations were decreased in the H group than the Con group, whereas the β-glucosidase and cellulase concentrations increased. Compared to the Con group, the relative abundance of propionate and butyrate in the H group was significantly higher. Higher relative abundance of Parabacteroides distasonis and Bacteroides thetaiotaomicron were observed with increasing OEO concentration. The function of rumen microbiota was enriched in the GH43_17 family, mainly encoding xylanase. Besides, metabolites, including heparin, pantetheine, sorbic acid, aspirin, and farnesene concentrations increased with increasing OEO dose. A positive correlation was observed between Parabacteroides distasonis, Bacteroides thetaiotaomicron, and β-glucosidase, cellulase and propionate. The abundance of Parabacteroides distasonis and Parabacteroides_sp._CAG:409 were positively correlated with sorbic acid and farnesene. In summary, OEO supplementation increased the rumen digestive ability by modulating epithelial development and microbiota composition in beef cattle. This study provides a comprehensive insight into the OEO application as an alternative strategy to improve ruminant health production.